The Relationship Between Pushing Position and the Incidence of Perineal Rupture in Primiparous Women at Independent Midwifery Practices (PMB) in the Ujung Berung Area in 2024 - Mulyani, Neng; Puspa Wati Manik, Tri Arini; Khairunnisa, Ika (Rifa'Institute, 2025)
Introduction: Perineal rupture during childbirth is a common cause of postpartum hemorrhage, especially among primiparous women. Pushing position during the second stage of labor may influence the likelihood of perineal injury. Objective: This study aimed to determine the relationship between pushing positions and the incidence of perineal rupture among primiparous women. Method: This analytical observational study involved 32 primiparous mothers who gave birth at independent midwifery practices (PMB) in the Ujung Berung region during December 2024. Data were collected using observation checklists and analyzed using Chi-square tests. Result and Discussion: The findings showed that among mothers who used the semi-sitting position, 68.4% had an intact perineum, while 53.2% of those who used the lithotomy position experienced a first-degree perineal rupture. The statistical analysis revealed a significant relationship between pushing position and the incidence of perineal rupture (p = 0.013). Conclusions: Pushing position during labor is significantly associated with the incidence of perineal rupture in primiparous women. The semi-sitting position is associated with a lower risk of perineal injury compared to the lithotomy position. Promoting optimal birthing positions could reduce maternal trauma during delivery.